The Intersection of Cybersecurity and Privacy in the Digital Age - Suresh Dameruppula (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This article explores the evolving relationship between cybersecurity and privacy in the digital landscape. It examines how organizations face growing challenges in managing data security while respecting individual privacy rights amid sophisticated threats and expanding regulatory frameworks. The article details multiple layers of cybersecurity protection including network, information, endpoint, application, and cloud security, alongside the evolving threat landscape of malware, phishing, and ransomware. It further explores privacy concepts beyond security, including data protection mechanisms, consent management approaches, transparency frameworks, and data minimization principles. The regulatory environment is discussed through examination of key frameworks including GDPR, CCPA/CPRA, and HIPAA. Finally, the article presents the convergence of security and privacy through integrated approaches including Privacy by Design, Zero Trust Architecture, and Data-Centric Security, highlighting how these complementary disciplines can work together to create robust protection in an increasingly interconnected digital ecosystem.